Prototype Sistem Keamanan Rumah Berbasis Mikrokontroler Menggunakan Multi Sensor - Luis Zefanya; Gideon Fercy Silitonga; Takwa Padang; Dian Putra Saragi; Eka Dodi Suryanto (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Current advances in knowledge and technology are driving people to think creatively. Similarly, the use of automation technology has advanced to the point where it can automate many daily activities. When automation is implemented on an ongoing basis, it can be leveraged to assist with routine tasks (Tullah et al., 2019). One of the most pressing applications of automation technology today is in the implementation of security systems. Security is essential everywhere and at all times—whether at home, at work, during daily activities, or while resting. One place that requires security is the home, which serves as a storage place for valuables; threats typically come from outside sources such as thieves and scammers (Apsari & Prapanca, 2018). This study aims to design and build a prototype of an IoT-based smart home security system using four different sensors, with the ESP32 serving as the system’s central processor, to effectively detect and respond to security threats. This system offers various benefits, such as enhanced security through accurate threat detection, rapid notifications regarding unwanted security incidents, improved well-being for residents, and the ability to monitor the home in real-time remotely via a smartphone app. The sensors used include a PIR sensor for motion detection, an MQ2 sensor for gas leak detection, an SW-420 sensor for earthquake vibration detection, and a GY-906 sensor for burning temperature detection. To enhance its mobility, the system is designed so that the overall performance of the sensors can be monitored using the Blynk app. This research consists of four stages: data collection, rapid prototyping, prototype design, and prototype testing.